AUTHENTIC MATERIALS IN TEACHING FOREIGN LANGUAGE - Komila Ruzieva Yangibaevna (American Journals Publishing, 2023)
In this article, we discuss the advantages and disadvantages of bringing authentic materials into the classroom, in the example of authentic texts, pictures. Preliminary issues of studying vocabulary and, in particular, clarify the importance and significance of using pictures in the course of mastering foreign vocabulary as one of the visual aids. In addition, we define the linguo-methodological foundations for using pictures and show the advantages of using them.
Keywords: Linguo-methodological foundations, visuals, comprehend, technical quality, speech activity.